Early evidence on genetic polymorphisms in conferring a "Two-Hit" propensity to renal injury in Asian Indian children - Suramya Anand; Minu Bajpai; Alok Kumar; Siddharth Kapahtia (Wolters Kluwer Medknow Publications, 2022)
Background: Congenital anomalies of the kidney and urinary tract (CAKUT) are a common cause of end-stage renal disease in children. While certain nephrogenic genes have been incriminated in these malformations, data to identify the frequency of gene polymorphisms in Asian Indian children with CAKUT are scarce. This study was done to identify the effect of polymorphisms in paired-box gene 2 (PAX2), bone morphogenetic protein (BMP)-4, angiotensin-converting enzyme (ACE), and angiotensin II receptor Type 2 (AGTR2) nephrogenic genes on the development of CAKUT. Materials and Methods: In this prospective cohort study, 158 children <12 years old (86 cases with CAKUT and 72 age-matched controls) were analyzed. DNA from both sets was extracted from peripheral blood using the Keygen DNA extraction kit, and single-nucleotide gene polymorphisms (SNPs) in PAX2, BMP-4, ACE, and AGTR2 nephrogenic genes were detected by polymerase chain reaction (PCR) using previously published primers and PCR conditions. Results: The presence of A allele SNP for AGTR2 gene at rs3736556 was found to be significantly correlated with the development of ureteropelvic junction obstruction and vesicoureteral reflux (VUR) with the TT allelic genotype having a lower incidence of pelviureteric junction obstruction (odds ratio [OR] 0.18 [95% confidence interval [CI], 0.06-0.55], P = 0.01) and VUR (OR 0.31 [95% CI, 0.11-0.91], P = 0.03). Furthermore, on substratification of the patients with the presence of the A allele of AGTR2, 24 out of 27 patients with scarring were found to harbor the D allele of the ACE gene, thus predisposing them to further renal damage. Conclusion: This study points to early evidence in the implication of nephrogenic genes in development as well as predisposition to renal injury in Asian Indian patients with CAKUT.